The deep sea: The new frontier for ecological restoration. (October 2019) - Da Ros, Zaira; Dell'Anno, Antonio; Morato, Telmo; Sweetman, Andrew K.; Carreiro-Silva, Marina; Smith, Chris J.; Papadopoulou, Nadia; Corinaldesi, Cinzia; Bianchelli, Silvia; Gambi, Cristina; Cimino, Roberto; Snelgrove, Paul; et al.
Abstract: Deep-sea ecosystems are the most extensive on Earth and provide key goods and services for human well-being, such as genetic resources and climate regulation. Maintaining the sustainable functioning of the global biosphere therefore requires protection of deep-sea ecosystems, particularly because these ecosystems face major changes related to human and climate-induced impacts. Although we lack data to evaluate the spatial scale of degraded deep-sea habitats, numerous studies document human impacts on the whole ocean. However, protection alone can be insufficient to reverse habitat degradation in the deep sea. Scientifically, deep-sea restoration actions may be feasible, but whether such actions will achieve sustainability goals when applied at broad spatial scales of impact remain questionable. Successful application of most restoration efforts will first require a deeper understanding of biodiversity and functioning of deep-sea ecosystems, and better knowledge of ecosystem resilience and recovery rates of deep-sea fauna. In addition to limited data availability, expensive technologies (with estimated costs up to millions of dollars ha −1 ) represent a major obstacle to large-scale deep-sea restoration, but international cooperation (like a stronger collaboration between industry and scientists belonging to the academia) could significantly reduce this operational cost. Future deep-sea ecosystem restoration could offer an important business opportunity for technological development and application and an investment in natural capital for a new and competitive blue-growth sector. Highlights: The deep sea includes the most extensive ecosystems of the world. Deep-sea habitats urgently require protection actions. Protection without restoration can be insufficient to reverse habitat degradation. More knowledge on ecosystem baselines is needed to restore. Scientists and industry could together provide feasible solutions to restore.